Management of Islamic Education Institutions in the Era of Globalization: An Analysis of Quality, Resources, and Social Dynamics - Masnawati, Eli; Hariani, Mila; Mardikaningsih, Rahayu; Nurhasanah, Nurhasanah; Sulipah, Sulipah (Bulletin of Science, Technology and Society, 2024)
Islamic Educational Institutions (IEI) play a vital role in shaping a generation of Muslims capable of navigating global challenges. However, this study identifies persistent issues affecting IEI, including low educational quality, curriculum gaps, limited human resources, and inadequate infrastructure. Social dynamics and evolving expectations of modern society further pressure IEI to remain relevant in the era of globalization. Management weaknesses—such as insufficient leadership capacity, reliance on traditional methods, and limited technological adoption—pose significant obstacles to institutional development. The aim of this research is to analyze strategic approaches for transforming IEI into more competitive and sustainable institutions. Using a literature review method, the study highlights the importance of curriculum reform, educator training, diversified funding, and modern technology integration. It also emphasizes the role of stakeholder engagement in enhancing strategic effectiveness. The findings offer a conceptual foundation to guide future efforts in improving the quality and resilience of Islamic educational institution.